ICT in Early Childhood Education. (Journal of Parents and Teachers, 2014)
This article exposes that ICT is the cornerstone in teacher education. Therefore, computer training programs and the design of an ICT training plan in the school center are included.
Keywords: ICT; resources; teachers´ formation.